2007
DOI: 10.1007/s11060-007-9488-y
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 as an autocrine stimulus in human T98G glioblastoma cells: role in cell growth and migration

Abstract: HMGB1 (high mobility group box 1 protein) is a nuclear protein that can also act as an extracellular trigger of inflammation, proliferation and migration, mainly through RAGE (the receptor for advanced glycation end products); HMGB1-RAGE interactions have been found to be important in a number of cancers. We investigated whether HMGB1 is an autocrine factor in human glioma cells. Western blots showed HMGB1 and RAGE expression in human malignant glioma cell lines. HMGB1 induced a dose-dependent increase in cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 46 publications
2
65
0
Order By: Relevance
“…[42][43][44] It is well established that exogenous HMGB1 induces MEK-ERK activation in immune cells and cancer cells. 19,22,32,45 Here, we found that 3-MA inhibited HMGB1-induced phosphorylation of ERK, indicating that ERK is a downstream signal of PI3K. Importantly, knockdown or pharmacological inhibition of MEK-ERK attenuated HMGB1-induced LC3 conversion, suggesting that MEK-ERK is also required for HMGB1-induced autophagy in leukemia cells.…”
Section: Discussionmentioning
confidence: 75%
“…[42][43][44] It is well established that exogenous HMGB1 induces MEK-ERK activation in immune cells and cancer cells. 19,22,32,45 Here, we found that 3-MA inhibited HMGB1-induced phosphorylation of ERK, indicating that ERK is a downstream signal of PI3K. Importantly, knockdown or pharmacological inhibition of MEK-ERK attenuated HMGB1-induced LC3 conversion, suggesting that MEK-ERK is also required for HMGB1-induced autophagy in leukemia cells.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, we show here that microglial cells receive signals from gliomas via TLRs. Gliomas can constitutively release heat-shock proteins, the high-mobility group box 1 protein, and hyluronan (23)(24)(25) and all these factors have been shown to stimulate TLRs (26). It is possible that these factors were present in our GCM, which was used to stimulate microglial MT1-MMP expression and activity in vitro.…”
Section: Glioma Cells Induce Microglial Mt1-mmp Expression Via Tlr Simentioning
confidence: 99%
“…The wound area was observed by microscopy (Olympus CK2) (magnifications, ϫ100). Relative cell migration distance was determined by measuring the wound width and subtracting this from the initial value as previously described: cell migration distance ϭ initial wound width at day 0 Ϫ wound width at the day of measurement (Bassi et al, 2008). A total of three areas were randomly selected and examined in each well.…”
Section: Cell Migration Assaysmentioning
confidence: 99%